New amber record of Braconidae (Insecta: Hymenoptera) from the mid-Cretaceous of Myanmar. (August 2021) - Li, Longfeng; Shih, Chungkun; Yang, Jingtao; Wang, Lixia; Li, Daqing; Ren, Dong
Abstract: Protorhyssalinae is an extinct, Cretaceous-only subfamily of braconid wasps hitherto comprising 7 genera and 7 species in its widest acceptance. A new genus Burmabracon gen. nov. with two new species, B. gracilens sp. nov. and B. grossus sp. nov. from the mid-Cretaceous Myanmar (Burmese) amber, are described and assigned to Protorhyssalinae, based on the following characters: head orthognathous and almost certainly cyclostome, antenna with more than 20 antennomeres, notauli complete, forewing with 2m-cu absent and hind wing with 1r-m and Cu present. The Mesozoic fossil record of the Braconidae suggests that the family originated in or before the Early Cretaceous.